MEASURING THE VALUE OF PUBLIC SECTOR AUDIT, CHALLENGES AND NECESSITY (Third Sector Social Economic Review, 2023)
The value of public sector audits has become increasingly important in an era of increased accountability, transparency and fiscal responsibility. Auditing the efficiency and effectiveness of public spending is essential for optimizing resources and ensuring efficient service delivery. However, measuring the value of audits presents challenges due to intangible outcomes and different stakeholder interests. The aim of this study is to reveal the difficulties and necessity of applying the approaches that are widely used in measuring the value of private audit activities to public sector auditing. In the study, starting from the theory of private sector auditing, the value of public auditing is evaluated within the scope of agency theory approach, public value approach, difference in accounting principles, audit failure approach, signaling approach, insurance approach and management control approach. While the agency theory approach, signaling approach, insurance approach, and management control approach are partially applicable to measuring the value of public sector audit, difficulties in applying other approaches have been revealed.
Keywords: Auditing; Public Sector; Private Sector; Value; Private Sector Audit Theories